THE ROLE OF INTERACTIVE AND IMMERSIVE LEARNING IN TEACHING FOREIGN LANGUAGE - Yuldasheva Dilafroz Bakhodirjon kizi (Web of Journals Publishing, 2025)
The need for innovative approaches to teaching foreign languages is becoming more evident in the context of globalization and technological advancement. Traditional methods, while still useful, often struggle to engage students in ways that promote long-term retention and practical language use. This article examines the role of interactive and immersive learning in the teaching of foreign languages, exploring its potential benefits, methods, challenges, and examples of effective application. It argues that by integrating technology, real-life contexts, and interactive elements, foreign language education can become more engaging, motivating, and effective for learners. The paper draws upon existing literature and case studies to demonstrate how these approaches can transform foreign language education in a rapidly changing world.
Keywords: Interactive learning, immersive learning, foreign language acquisition, language immersion, technology in language learning, language learning tools, digital platforms, cultural immersion, student engagement, multimedia resources, simulations.